KONFLIK BATIN TOKOH MORIGUCHI YUUKO DALAM FILM CONFESSION KARYA TETSUYA NAKASHIMA - Ni Luh Kristy Ariani; Wayan Nurita; Anak Agung Ayu Dian Andriyani (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2022)
The research